Integrasi Nilai Amanah dan Khalifah dalam Akuntansi Pertanggungjawaban Syariah: Systematic Literature Review - Wa Ode Hasriana; Nur Istiqomah; Tujiono; Oktaviani Indah kurniasari; Rustam Hanafi (CV. Doki Course and Training, 2026)
This study aims to examine the integration of amanah and khalifah values into Islamic responsibility accounting. The topic is important because responsibility accounting is not only related to performance measurement and financial reporting, but also to moral, social, and spiritual responsibilities in resource management. This study applies a systematic literature review method using the PRISMA approach. The literature was collected from Scopus, SINTA, and Google Scholar within the publication period of 2015-2026. Out of 479 identified articles, 25 articles met the inclusion criteria and were analyzed thematically. The findings show that amanah emphasizes honesty, integrity, transparency, and accountability to Allah SWT and stakeholders. Khalifah positions humans as stewards of resources who are responsible for justice, sustainability, and public welfare. The integration of these values produces a dual accountability paradigm, namely vertical accountability to Allah SWT and horizontal accountability to humans, organizations, society, and the environment. This study also identifies several implementation challenges, including limited Islamic accounting literacy, insufficient non-financial reporting standards, and the need to strengthen human resource competencies. The findings contribute conceptually to the development of responsibility accounting based on Islamic values and provide a foundation for future empirical studies. Abstrak Penelitian ini bertujuan untuk mengkaji integrasi nilai amanah dan khalifah dalam akuntansi pertanggungjawaban syariah. Topik ini penting karena akuntansi pertanggungjawaban tidak hanya berkaitan dengan pengukuran kinerja dan pelaporan keuangan, tetapi juga dengan tanggung jawab moral, sosial, dan spiritual dalam pengelolaan sumber daya. Penelitian menggunakan metode systematic literature review dengan pendekatan PRISMA. Literatur diperoleh melalui Scopus, SINTA, dan Google Scholar dengan rentang publikasi 2015-2026. Dari 479 artikel yang teridentifikasi, 25 artikel memenuhi kriteria inklusi dan dianalisis secara tematik. Hasil kajian menunjukkan bahwa nilai amanah menekankan kejujuran, integritas, transparansi, dan tanggung jawab kepada Allah SWT serta pemangku kepentingan. Nilai khalifah menempatkan manusia sebagai pengelola sumber daya yang wajib menjaga keadilan, keberlanjutan, dan kemaslahatan. Integrasi kedua nilai tersebut menghasilkan paradigma akuntabilitas ganda, yaitu akuntabilitas vertikal kepada Allah SWT dan akuntabilitas horizontal kepada manusia, organisasi, masyarakat, serta lingkungan. Penelitian ini juga menemukan tantangan implementasi berupa keterbatasan literasi akuntansi syariah, belum optimalnya standar pelaporan non-keuangan, dan perlunya penguatan kompetensi sumber daya manusia. Temuan ini memberikan kontribusi konseptual bagi pengembangan akuntansi pertanggungjawaban berbasis nilai Islam dan menjadi dasar bagi penelitian empiris selanjutnya.